Dynamic Governance in the Development of Santri City in Bireuen District - Nofica, Idza; Yani, Ahmad; Alfiady, Teuku Alfiady; Syamsuddin, Syamsuddin; Muryali, Muryali (LPPM Universitas Malikussaleh, 2024)
This study examines the concept of Dynamic Governance in Bireuen District regarding the designation of Bireuen as